2022
DOI: 10.3390/healthcare10071287
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based (Mhealth) and Standard/Traditional Maternal Care for Pregnant Woman: A Systematic Literature Review

Abstract: The world of health has changed significantly since the advent of smartphones. Smartphones have been widely known to facilitate the search for health information in the mobile Health (mHealth) system, which is used to improve the quality of life for patients, such as communication between doctors and patients. This systematic literature review aims to identify the use of mHealth as a digital communication tool for pregnant women by comparing technology-based and standard-based pregnancy care. The method used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…SLPs indicated they tend to restrict the use of mHealth technology to answering patients' questions. In recent years, mHealth technology has become a communication tool between physicians and patients and has led to the exchange of information between them [19]. Digital communication can improve patients' satisfaction as, in some instances, it reduces the need for face-to-face visits, for example when a patient needs to ask a question of a nonmedical nature [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…SLPs indicated they tend to restrict the use of mHealth technology to answering patients' questions. In recent years, mHealth technology has become a communication tool between physicians and patients and has led to the exchange of information between them [19]. Digital communication can improve patients' satisfaction as, in some instances, it reduces the need for face-to-face visits, for example when a patient needs to ask a question of a nonmedical nature [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…mHealth is a promising solution in pregnancy care compared to the standard of maternal care. One of the benefits of mHealth is the media that can be used for digital health communication in telemidwifery [ 41 ]. Midwives need telemidwifery to provide health education services for clients ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, there have been several applications that midwives have used to provide mother–child health (MCH), such as e-cohort [ 36 ], Tele-CTG [ 37 ], iPosyandu [ 38 ], Continuum of Care Services (CCS) [ 39 ], and Traditional Birth Attendants (TBAs) mHealth for traditional attendance [ 40 ]. However, recent literature reviews found limited specific mHealth for midwives since most of them are focused on clients’ services [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones have been widely known to facilitate the search for health information in the mobile Health known as mHealth system, which is used to improve the quality of life for patients, such as communication between doctors and patients (Kusyanti et al, 2022). Electronic health known as eHealth refers to computer-based services, while mHealth applies to mobile systems with specialized features to improve health care delivery (Aljohani and Chandran, 2021).…”
Section: Introductionmentioning
confidence: 99%